2017
DOI: 10.20884/1.jm.2017.12.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Free Radical Scavenging Activity in Ethanolic Extract from Promising Accessions of Curcuma aeruginosa RoxB.

Abstract: This study evaluated the antioxidant activity through the determination of free radical scavenging activity of ethanolic extracts from 20 accessions of Curcuma aeruginosa, and it is to use for the development of varieties in future. The radical scavenging activity of the extract accessions was investigated with 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical. IC 50 values for DPPH radical scavenging activity ranged from 89.81 to 505.65 µg mL -1 . Based on IC 50 values, twenty accessions of C. aeruginosa can be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…For this reason, Trolox can be considered as the proper counterpart of Vitamin E to examine its actions in aqueous radical environments on its own and in combination with other antioxidant compounds. For 2,2-diphenyl picrylhydrazyl (DPPH) method proposed by Nurcholis et al 51 , with modification. Briefly, 100 µl O. aristatus ethanol extract was added to 100 µl of 125 µM DPPH in methanol at the 96-well microplate (Costar-USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, Trolox can be considered as the proper counterpart of Vitamin E to examine its actions in aqueous radical environments on its own and in combination with other antioxidant compounds. For 2,2-diphenyl picrylhydrazyl (DPPH) method proposed by Nurcholis et al 51 , with modification. Briefly, 100 µl O. aristatus ethanol extract was added to 100 µl of 125 µM DPPH in methanol at the 96-well microplate (Costar-USA).…”
Section: Methodsmentioning
confidence: 99%
“…For 2,2-diphenyl picrylhydrazyl (DPPH) method proposed by Nurcholis et al 51 , with modification. Briefly, 100 µl O. aristatus ethanol extract was added to 100 µl of 125 µM DPPH in methanol at the 96-well microplate (Costar-USA).…”
Section: Methodsmentioning
confidence: 99%
“…Ten rhizomes of Curcuma aeruginosa accessions were obtained from result selection of previous research, samples collected from different regions in East Java, Central Java, Yogyakarta, West Java and Jambi in February 2015, based on metabolites contents and biological activities [10,[21][22][23]. Ten C. aeruginosa accessions were namely given codes with KL (Klewer), PK (Pakem), BH (Beringharjo), GK (Gunung Kidul), KP (Kulonprogo), PW (Purworejo), MD (Madura), LC (Losari Cirebon), CB (Ciampea Bogor) and MB (Muara Bungo).…”
Section: Methodsmentioning
confidence: 99%
“…The metabolism and accumulation of secondary metabolites in the medicinal plant influenced by genetic and environmental factors [20]. Previous studies [8,10,21] showed the existence of different curcuminoids contents and pharmacological activities of Curcuma aeruginosa accessions from different location of Indonesia. The information of curcuminoids contents of Curcuma aeruginosa accessions were still limited as they cultivated in the same environmental conditions.…”
mentioning
confidence: 99%
“…C. aeruginosa contains several bioactive compounds such as flavonoid, phenolic acids (Nurcholis et al 2016b), curcumin, demethoxycurcumin and bisdemethoxycurcumin (Nurcholis et al 2019(Nurcholis et al , 2016a, germacrone (Hossain et al 2015;Srivilai et al 2018), isocurcumenol, zederone, curcumenol, dehydrocurdione, zedoarondiol (Suphrom et al 2012), tropolone, eucalyptol, and curcumol (Fitria et al 2019). The reported biological activities of C. aeruginosa and its metabolites include antimicrobial (Akarchariya et al 2017), analgesic effect (Reanmongkol et al 2006), antiandrogenic (Suphrom et al 2012), uterine relaxant effect (Thaina et al 2009), antioxidant (Nurcholis et al 2017), antinociceptive (Hossain et al 2015), hair growth promotor (Pumthong et al 2012), and anticancer (Fitria et al 2019). Therefore, it is crucial to select C. aeruginosa accessions with high phytochemical content and high pharmacological activities, which can be developed for plant breeding programs.…”
Section: Introductionmentioning
confidence: 99%